Crystallographic Characterization of Cleavage Plane in Low-carbon Martensitic Steel. (2015) - Tsuboi, M.; Shibata, A.; Terada, D.; Tsuji, N.
Abstract: The present study determined the crystallographic orientation of the cleavage plane in a low-carbon martensitic steel by two different methods using electron backscattering diffraction (EBSD) orientation analysis and three-dimensional imaging technique. One is the direct measurement of the cleavage plane by EBSD after tilting the specimen in SEM based on the line profiles of the 3D fracture surface image. The other is the trace analysis on EBSD orientation maps just beneath the fracture surface and the line profiles of the 3D fracture surface image. The both two methods demonstrated that cleavage fracture occurred on {001} planes in martensitic steel.